2011
DOI: 10.1007/s00792-011-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

The major lipid cores of the archaeon Ignisphaera aggregans: implications for the phylogeny and biosynthesis of glycerol monoalkyl glycerol tetraether isoprenoid lipids

Abstract: The lipid cores from Ignisphaera aggregans, a hyperthermophilic Crenarchaeon recently isolated from New Zealand hot springs, have been profiled by liquid chromatography-tandem mass spectrometry. The distribution revealed includes relatively high proportions of monoalkyl (also known as H-shaped) tetraether cores which have previously been implicated as kingdom-specific biomarkers for the Euryarchaeota. Such high expression of monoalkyl tetraether lipids is unusual in the archaeal domain and may indicate that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 57 publications
4
48
0
Order By: Relevance
“…Methylated lipids were not detected in extracts from other Crenarchaeota , including other species of Sulfolobus ( S. shibatae and S. solfataricus ) and species of Ignisphaera ( I. aggregans AQ1.S1 T and I. sp. Tok37.S1) . Thus, there appears to be some taxonomic specificity for production of methylated tetraethers by Crenarchaeota , including at the species level in Sulfolobus .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Methylated lipids were not detected in extracts from other Crenarchaeota , including other species of Sulfolobus ( S. shibatae and S. solfataricus ) and species of Ignisphaera ( I. aggregans AQ1.S1 T and I. sp. Tok37.S1) . Thus, there appears to be some taxonomic specificity for production of methylated tetraethers by Crenarchaeota , including at the species level in Sulfolobus .…”
Section: Resultsmentioning
confidence: 98%
“…[20] Liquid chromatography-tandem mass spectrometry of lipid cores Lipid cores were analysed by normal phase LC-MS/MS using a Dionex Ultimate 3000 RSLC liquid chromatograph coupled to a Bruker HCTultra ETD II ion trap mass spectrometer equipped with an atmospheric pressure chemical ionisation (APCI) source. Conditions for analyses of lipids from the organisms were modified from Knappy et al [9] following consideration of Peterse et al [41] Separation was achieved at 30°C using a Waters Spherisorb S3-CN (2.0 × 150 mm; 3 μm) column and a binary gradient programme (A = hexane, B = 90 : 10 (v/v) hexane : isopropanol), with flow rate 0.15 ml min À1 and solvent proportions of 90% A, 10% B (0-5 min) and 84% A, 16% B (at 39 min). Following each analysis, the column was flushed at 0.7 ml min À1 with isopropanol : methanol (1 : 1 v/v) for 2 min to clean the column, and with 90% A, 10% B for 15 min to recondition.…”
Section: Soils and Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high abundances of GTGTs in HWCG‐III Thaumarchaeota are unprecedented among cultivated archaea (Table ; cf. De Rosa and Gambacorta, ; Knappy et al ., ; Feyhl‐Buska et al ., ) and have previously been interpreted to reflect sub‐optimal growth conditions of Ca. N. yellowstonii (cf.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, M-Ar core lipids were originally identified in the methanogenic archaeon Methanocaldococcus jannaschii (Comita et al, 1984) and similarly H-GDGT lipids were originally identified in the hyperthermophilic methanogen, Methanothermus fervidus (Morii et al, 1998). and more recently, the crenarchaeon Ignisphaera aggregans (Matsuno et al, 2009;Jahn et al, 2004;Knappy et al, 2011;Reysenbach et al, 2006;Schouten et al, 2008). Likewise, H-GDGTs are known to be produced by other non-methanogenic deepsea hydrothermal vent Euryarchaeota such as Ignicoccus spp., Aciduloprofundum boonei, Thermococcus sp.…”
Section: Sources Of Archaeal-iplsmentioning
confidence: 99%